Static Magnetic Field Reduces the Anticancer Effect of Hinokitiol on Melanoma Malignant Cells-Gene Expression and Redox Homeostasis Studies - Agnieszka Synowiec-Wojtarowicz; Agata Krawczyk; Magdalena Kimsa-Dudek (MDPI AG, 2024)
Background: Melanoma malignant is characterized by a high mortality rate, accounting for as much as 65% of deaths caused by skin cancer. A potential strategy in cancer treatment may be the use of natural compounds, which include hinokitiol (β-Thujaplicin), a phenolic component of essential oils extracted from cypress trees. Many studies confirm that a high-induction SMF (static magnetic field) has anticancer effects and can be used as a non-invasive anticancer therapy in combination with or without drugs. Aim: The aim of this experiment was to evaluate the effect of a static magnetic field on melanoma cell cultures (C32 and COLO 829) treated with hinokitiol. Methods and Results: Melanoma cells were exposed to a static magnetic field of moderate induction and hinokitiol. The research included determining the activity of the antioxidant enzymes (SOD, GPx, and CAT) and MDA concentration as well as the gene expression profile. Conclusion: Hinokitiol disturbs the redox homeostasis of C32 and COLO 829 melanoma malignant cells. Moreover, a static magnetic field has a protective effect on melanoma malignant cells and abolishes the anticancer effect of hinokitiol.